Music as a Medium of Instruction (MMI): A new pedagogical approach to English language teaching for students with and without music training - Fernández de Cañete García, Claudia; Pineda-Hernández, Inmaculada Concepción; Waddell, George (Sage, 2022)
Recent research shows that musical training improves children’s development of oral and aural skills. This study focuses on developing and testing a methodological framework (Music as a Medium of instruction, MMI) in English language teaching (ELT) by contrasting MMI and gamification methodologies with the participation of 22 Spanish children all born in 2008. The differences in progression between participants with and without previous instrumental training are also discussed. Generalized linear model procedures were used for each outcome variable (listening comprehension and oral production skills) to investigate the effect of independent variables (MMI vs. gamification; students with music training vs. learners without music training). Results revealed that students of the MMI group had significantly higher scores than the gamification group in oral production. Significant improvement was traced in listening comprehension in the MMI group. This study provides promising initial evidence that the MMI approach can be at least as beneficial as gamification-based approaches for young learners in the ELT classroom. However, results need to be established on firmer grounds, for instance by using fully randomized experimental designs and by conducting mediation analyses.
Keywords: Inglés - Estudio y enseñanza; Enseñanza - Innovaciones; English language teaching; Musical training; Instrumental training; Gamification; Methodological innovations in language teaching